Demonstrasi Mahasiswa, Aktualisasi Diri dan Komunikasi Publik - Muhamad Abas; Arif Nur Alam (Jurnal Deliberatif, 2023)
Student demonstrations have historically often been successful in encouraging change. Until now, students are still believed to be agents of change based on moral strength, such as in demonstrations carried out by students on the Halu Oleo University campus. Demonstrations on campus are not only related to national issues but also local issues that occur on campus such as lecture facilities and increases in tuition fees. The perpetrators of student demonstrations on campus generally know and are aware that there is something wrong with the campus management system and practices. Demonstrations are considered as a means of public communication for students to convey their aspirations to campus officials when dialogue is ineffective, as well as an instrument of actualization after establishing themselves in lecture halls and intra/extra campus student institutions. There are many factors behind student demonstrations on campus, namely awareness within students, especially activists, to carry out a controlling role based on moral strength to encourage good campus governance and clean governance, the application of theoretical knowledge and experience when interacting on campus. and student institutions. in an effort to build a social movement. External interaction factors in organizing ideas and knowledge to always be critical in responding to various social facts that occur around them, both related to students' self-interest and the interests of society. Therefore, campuses must become role models in implementing democratic life by ensuring demonstration activities as a means of self-actualization and public communication for students.